Oomycete small RNAs bind to the plant RNA-induced silencing complex for virulence - Florian Dunker; Adriana Trutzenberg; Jan S Rothenpieler; Sarah Kuhn; Reinhard Pröls; Tom Schreiber; Alain Tissier; Ariane Kemen; Eric Kemen; Ralph Hückelhoven; Arne Weiberg (eLife, 2020)
The exchange of small RNAs (sRNAs) between hosts and pathogens can lead to gene silencing in the recipient organism, a mechanism termed cross-kingdom RNAi (ck-RNAi). While fungal sRNAs promoting virulence are established, the significance of ck-RNAi in distinct plant pathogens is not clear. Here, we describe that sRNAs of the pathogen Hyaloperonospora arabidopsidis, which represents the kingdom of oomycetes and is phylogenetically distant from fungi, employ the host plant’s Argonaute (AGO)/RNA-induced silencing complex for virulence. To demonstrate H. arabidopsidis sRNA (HpasRNA) functionality in ck-RNAi, we designed a novel CRISPR endoribonuclease Csy4/GUS reporter that enabled in situ visualization of HpasRNA-induced target suppression in Arabidopsis. The significant role of HpasRNAs together with AtAGO1 in virulence was revealed in plant atago1 mutants and by transgenic Arabidopsis expressing a short-tandem-target-mimic to block HpasRNAs, that both exhibited enhanced resistance. HpasRNA-targeted plant genes contributed to host immunity, as Arabidopsis gene knockout mutants displayed quantitatively enhanced susceptibility.